2020
DOI: 10.1021/acsanm.0c00843
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Coated Reduced Graphene Oxide Fiber Mesh-Polymer Composite Films for Electromagnetic Interference Shielding

Abstract: Expected to become mainstream in the electronics industry, flexible electronics still face major challenging issues. For polymeric-based flexible electronic substrates in particular, these challenges include a lack of electromagnetic shielding capability and poor heat dissipation. Here, we report a highly flexible and thermally conductive macroscopic polydimethylsiloxane (PDMS) polymer film embedded with a copper-coated reduced graphene oxide (rGO) fiber mesh. The rGO fibers are assembled into 3D fiber meshes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The results show that the graphene/epoxy composite shows a σ of 0.1 S cm −1 and an EMI SE of 21 dB when the content of graphene is 15 wt%. Li et al [ 68 ] embedded a copper-plated graphene fiber mesh into the PDMS film, and the results showed that the σ and EMI SE of PDMS film reached 3.21 × 10 5 S m −1 and 74 dB, respectively. Gu et al [ 69 ] prepared the silver nanowire (AgNW)/CNF composite film by the combination of vacuum-assisted filtration and hot pressing.…”
Section: Classification Of Emi Shielding Materialsmentioning
confidence: 99%
“…The results show that the graphene/epoxy composite shows a σ of 0.1 S cm −1 and an EMI SE of 21 dB when the content of graphene is 15 wt%. Li et al [ 68 ] embedded a copper-plated graphene fiber mesh into the PDMS film, and the results showed that the σ and EMI SE of PDMS film reached 3.21 × 10 5 S m −1 and 74 dB, respectively. Gu et al [ 69 ] prepared the silver nanowire (AgNW)/CNF composite film by the combination of vacuum-assisted filtration and hot pressing.…”
Section: Classification Of Emi Shielding Materialsmentioning
confidence: 99%
“…It was observed that being lightweight and nonconductive, graphene-based composites can absorb 99.99% of electromagnetic waves, whereas most metal-based composites simply redirect the radiations. Li et al [ 127 ] formed a copper-coated RGO@PDMS polymer composite by the Hummers method, where a shielding effectiveness of 74.2 dB was achieved in the X-band frequency range. Ni et al [ 128 ] synthesized a graphene aerogel (GA) with PDMS polymer, where shielding effectiveness of 60 dB was achieved within the frequency range of 2–18 GHz.…”
Section: Polymer-based Compositesmentioning
confidence: 99%
“…Research on graphene and polymer foam composites has been reported in recent years, Li embedded a copper-plated graphene fiber mesh into the PDMS film, and the results showed that the EMI SE of PDMS film reached 74 dB. 11 Zhang prepared the PMMA/graphene nanoplates (GNPs)/multi-walled carbon nanotubes (MWCNTs) composites with porous structures by using MWCNTs and GNPs and the results show that the EMI SE of the porous composites reaches 36 dB when the contents of MWCNTs and GNPs are 4 and 1.5 wt%, respectively, which is much higher than that of the homogeneous composites were prepared. 12 Eswaraiah prepared the functionalized graphene (f-G)/PVDF composites with a porous structure by chemical foaming using functionalized graphene (f-G) as the conductive filler and polyvinylidene fluoride (PVDF) as the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%